Accelerations of public transport vehicles: A method to derive representative generic pulses for passenger safety testing - Keller, Arne; Krašna, Simon (Frontiers in Future Transportation, 2023)
Investigating the postural balance and stability of standing passengers of public transport in laboratory or numerical tests requires generic test pulses, which replicate the acceleration/deceleration characteristics of common public transport vehicles such as buses or trams. We propose a method to generate such test pulses based on measured acceleration time series. The method consists of an automated splitting algorithm, an expansion in Legendre polynomials and a weighted mean to obtain average pulses which are not dominated by the events of highest magnitude. As a demonstration, the method is applied to acceleration time series obtained on public buses in normal operation, resulting in scalable generic pulse shapes. These can be used as the basis of a standardised framework for physical and virtual testing addressing the standing passenger problem.